Lead, Drive, and Thrive in the System - Mensik Kennedy, Jennifer, 1976- (Silver Spring, Maryland : American Nurses Association, 2023)
Nurses Are Natural Leaders. Whether you are new to a health care system or working to make change in your current system, Lead, Drive & Thrive in the System, 2nd Edition is your how-to guide to success. You can be a leader, and this book will show you how!
Chapter 4. Innovation and Standardization -- Innovation in Health Care Organizations -- The Difference between Knowledge Generation and Translation -- Setting the Stage for Innovation -- Diffusion of Innovation -- Design Thinking and Hackathons -- Hackathons -- Standardization in Health Care Organizations -- Creativity without Stifling -- Key Points -- Chapter 5. Facilitating and Managing Change -- Change and Organizations: Processes and Theories -- Change Agents -- Change Theories -- GE Change Acceleration Process (CAP) -- A Personal Note about Change Theories -- Shared Leadership and Bureaucracy.
Online resource; title from PDF title page (EBSCO, viewed April 23, 2024).
Includes bibliographical references and index.
OCLC control number change
Keywords: Nursing -- Practice -- United States; Soins infirmiers -- Pratique -- États-Unis.